2019
DOI: 10.1073/pnas.1911460116
|View full text |Cite
|
Sign up to set email alerts
|

Autism spectrum traits predict higher social psychological skill

Abstract: Social-cognitive skills can take different forms, from accurately predicting individuals’ intentions, emotions, and thoughts (person perception or folk psychology) to accurately predicting social phenomena more generally. Past research has linked autism spectrum (AS) traits to person perception deficits in the general population. We tested whether AS traits also predict poor accuracy in terms of predicting generalized social phenomena, assessed via participants’ accuracy at predicting social psychological phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
22
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 19 publications
(36 reference statements)
3
22
0
1
Order By: Relevance
“…Following previous theory (9), we suspect that different autistic traits have divergent associations with social psychological knowledge. Indeed, some traits are linked to greater social knowledge in line with Gollwitzer et al (1); however, others are associated with lower scores (Table 1). Broadly speaking, nonsocial traits are linked to better performance, whereas social traits are negatively related to social psychological knowledge.…”
supporting
confidence: 77%
See 2 more Smart Citations
“…Following previous theory (9), we suspect that different autistic traits have divergent associations with social psychological knowledge. Indeed, some traits are linked to greater social knowledge in line with Gollwitzer et al (1); however, others are associated with lower scores (Table 1). Broadly speaking, nonsocial traits are linked to better performance, whereas social traits are negatively related to social psychological knowledge.…”
supporting
confidence: 77%
“…We examined Gollwitzer et al’s (1) study on autism and better social psychological knowledge with interest, given its large samples and open dataset. We commend the authors for raising the bar for autism research, which is typically underpowered and rarely draws on social psychology.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, there has been an increased use of the AQ10 in large-scale studies to measure autistic traits in the general population. Specifically, overall AQ10 scores are being used to quantify the number of autistic traits/tendencies self-reported by an individual, and then correlated with their performance on other tasks (e.g., social psychological skill [Gollwitzer et al, 2019]).…”
Section: Introductionmentioning
confidence: 99%
“…Gollwitzer, et al . demonstrated that the inability of ASD cases to perceive individual intention, emotion, and thoughts is uniquely distinct (and indeed oppositely correlated) from the ability of ASD cases to predict social phenomena more generally [ 30 ]. Importantly, this observation was observed across data from 104 countries suggesting that culturally-driven social norms do not confound this skill.…”
Section: Discussionmentioning
confidence: 99%